Cognitive and emotional differentiators for beer: An exploratory study focusing on "uniqueness". (December 2016) - Cardello, Armand V.; Pineau, Benedicte; Paisley, Amy G.; Roigard, Christina M.; Chheang, Sok L.; Guo, Lindy F.; Hedderley, Duncan I.; Jaeger, Sara R.
Highlights: Consumers characterised beers by attitudinal, situational and emotional measures. Familiar beers were "ordinary", "simple", and "boring", and for "casual/everyday" situations. Novel beers were "unusual", "intriguing", and "complex", and for "special occasions". "Unique" beers had unusual characteristics, positive hedonic and emotional associations. "Unique beers" were appropriate for use in a variety of consumption situations. Abstract: The current explosion of micro-brewed beers has created a category that varies greatly in style, quality, ingredients, sensory attributes and brand images. To establish a niche in this market, brewers often differentiate their product through the tailoring of sensory characteristics of the beer or its brand image. However, many other consumer-based attitudinal and cognitive variables can be used to differentiate beers. These include perceived familiarity, novelty and situational appropriateness, as well as attitudinal and emotional product associations. In the present study, these variables were evaluated for their effectiveness in differentiating a variety of New Zealand beers. Two sets of 8 beers were evaluated by consumers (n = 203 beer enthusiasts) by: (i) classifying them for familiarity/novelty, (ii) answering attitudinal questions, (iii) assessing appropriateness for 15 common use situations and (iv) identifying emotional associations. Results showed each of the variables to be important differentiators. Although perceived familiarity and novelty were inversely related, familiarity better differentiated among the familiar beers, while novelty better differentiated the novel beers. Attitudinal data showed the most familiar beers to be "ordinary", "boring" and "simple", and those judged novel to be "unusual", "intriguing", and "complex". In spite of this, "appealing" beers could be found among both the familiar and novel samples. Situational appropriateness data showed familiar beers to be appropriate for "casual" and "everyday" situations, while novel beers were most appropriate for "special occasions". Lastly, emotion data showed the beers to differ along "active/passive" and "hedonic" dimensions, with familiar beers having passive emotional associations and novel beers having more active associations. In summary, this novel, consumer-based multi-faceted approach was extremely effective in differentiating among beers and provided useful insights for the identification of what may be considered "unique" beers.